2019
DOI: 10.18203/2349-3933.ijam20194228
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression among nurses working in a tertiary care hospital in South India

Abstract: Background: Nursing binds human society with a bond of care and affection. Nurses are often the first healthcare professional that patients meet. Quality of care for patients is strongly linked to the performance of the nursing staff. If the mental health status of these nurses is troubled, then they will not be able to give their full attention to this demanding task. Nowadays, all efforts to fight health workers’ illnesses are extremely important. This descriptive cross-sectional study will give us knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
4
16
0
1
Order By: Relevance
“…23 Educational status was not associated with anxiety and depression among nurses in India. 24 Marital status was not associated with depression, anxiety and stress in this study which is supported by the Iranian study. 21 Duration of work was not associated with depression, anxiety and stress in our study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…23 Educational status was not associated with anxiety and depression among nurses in India. 24 Marital status was not associated with depression, anxiety and stress in this study which is supported by the Iranian study. 21 Duration of work was not associated with depression, anxiety and stress in our study.…”
Section: Discussionsupporting
confidence: 83%
“…23 A study conducted among nurses working in a tertiary care hospital of India showed that anxiety and depression levels are increased in the younger and less experienced nurses. 24 Likewise, working unit had significant association with depression, anxiety and stress which is supported by a study among health care workers revealing that those working in higher risk areas were found more likely to have depression. 19 This finding is also supported by a study among Hongkong nurses where specialty of nursing had significant association with depression, anxiety and stress.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This setting was selected because of the rural population consider this hospital as central and has a low level of financial cost so, nurses were stressed and overload in their shifts. with patients' family members (Shajan & Nisha, 2019;Maharaj et al, 2018).…”
Section: Research Settingsmentioning
confidence: 99%
“…Depression is portrayed by slowing down of psychic processes, depressive and/or irritable mood, decreased energy, disinterest, apathy, concentration difficulty, negative thinking, with a loss of planning capacity and altered judgments of truth. Nurses experienced burdensome indications twice more than people's rate in different callings (Shajan & Nisha, 2019). Presenteeism is the efficiency misfortune that happens when laborers are available grinding away, however, are not working at top execution in view of medical conditions.…”
Section: Research Settingsmentioning
confidence: 99%